Removal of residual nuclei following a cavitation event using low-amplitude ultrasound - Duryea, Alexander P (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2014)
Microscopic residual bubble nuclei can persist on the order of 1 s following a cavitation event. These bubbles can limit the efficacy of ultrasound therapies such as shock wave lithotripsy and histotripsy, because they attenuate pulses that arrive subsequent to their formation and seed repetitive cavitation activity at a discrete set of sites (cavitation memory). Here, we explore a strategy for the removal of these residual bubbles following a cavitation event, using low-amplitude ultrasound pulses to stimulate bubble coalescence. All experiments were conducted in degassed water and monitored using high-speed photography. In each case, a 2-MHz histotripsy transducer was used to initiate cavitation activity (a cavitational bubble cloud), the collapse of which generated a population of residual bubble nuclei. This residual nuclei population was then sonicated using a 1 ms pulse from a separate 500-kHz transducer, which we term the bubble removal pulse. Bubble removal pulse amplitudes ranging from 0 to 1.7 MPa were tested, and the backlit area of shadow from bubbles remaining in the field following bubble removal was calculated to quantify efficacy. It was found that an ideal amplitude range exists (roughly 180 to 570 kPa) in which bubble removal pulses stimulate the aggregation and subsequent coalescence of residual bubble nuclei, effectively removing them from the field. Further optimization of bubble removal pulse sequences stands to provide an adjunct to cavitation-based ultrasound therapies such as shock wave lithotripsy and histotripsy, mitigating the effects of residual bubble nuclei that currently limit their efficacy